PEMBERDAYAAN EKONOMI KELUARGA: WORKSHOP MANAJEMEN KEUANGAN BERSAMA PKK DESA MAYONG LOR JEPARA - Jumaiyah, Jumaiyah; Wahidullah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Good financial management within families is essential for improving community welfare, especially at the village level. This community service program aimed to empower families economically through a financial management workshop conducted in collaboration with the Women’s Family Welfare Program (PKK) of Mayong Lor Village, Jepara. The program involved 30 active PKK members and employed structured training methods coupled with continuous mentoring. Data collection was carried out through pre-tests and post-tests, observations, implementation, monitoring, and evaluation over a three-month period.The results of the program demonstrated a 65% increase in participants’ financial literacy, with 85% of participants routinely maintaining financial records. Behavioral changes in financial management were indicated by 75% of participants establishing regular savings, 60% successfully separating business and household finances, and 45% beginning to invest. This community service initiative has proven that a community-based economic empowerment model, integrating financial literacy, business development, and strengthening local capacities, is effective in improving family welfare at the village level.